THE PERCEPTION OF D3 HOSPITALITY STUDENTS AT STIEPARI SEMARANG ON THE IMPORTANCE OF ENGLISH PROFICIENCY IN HOTEL AND RESTAURANT CAREERS: A QUANTITATIVE STUDY - Ade Prabowo, Bayu; Adhistyo Wijoyo, Tuwuh; Abdul Jabbar, Umar; Andriani Putri, Julian (Universitas PGRI Palembang, 2025)
This study examined the perceptions of D3 Hospitality students at STIEPARI Semarang regarding the importance of English proficiency for careers in the hotel and restaurant industries, as well as the factors influencing these views. A quantitative descriptive survey was conducted with 44 students using a 5-point Likert scale questionnaire covering four dimensions: awareness of English importance, self-assessed readiness, learning barriers, and institutional expectations. Data were analyzed using SPSS. Findings indicated that students generally perceived English as highly important (M = 3.86), particularly for guest communication and career advancement (M = 4.32). Speaking and listening skills were prioritized over reading and writing. However, students reported moderate confidence in their English abilities (M = 3.14), especially in understanding accents and speaking fluently. Major challenges included limited vocabulary and a lack of practice opportunities. Students with internship experience showed significantly higher perception scores (M = 4.15) compared to those without (M = 3.64), highlighting the value of practical exposure. The study suggests that hospitality education institutions should emphasize communicative approaches, incorporate industry-specific training, and provide early practical experiences to enhance students' readiness for the global hospitality sector.